2014
DOI: 10.1371/journal.pone.0106130
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Uric Acid and Coronary Artery Disease in Premenopausal Women

Abstract: ObjectiveTo date, no study in the published literature has investigated the role of various serum uric acid (SUA) concentrations in the development of angiographically-proven coronary artery disease (CAD) in premenopausal women. Therefore, the aim of this study was to investigate the role SUA levels may play in the prevalence, severity, and prognosis of CAD in premenopausal women.MethodsThis cross-sectional retrospective study included 607 premenopausal women who had undergone coronary angiography. The CAD dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 27 publications
1
21
2
1
Order By: Relevance
“…[23] The increased serum uric acid level was also found to be associated with the severity of CAD in both men and women. In the present study significant relationship was observed between uric acid and CAD similar results were reported from a study with 1012 patients who underwent coronary angiography in Turkish population, [24] cross-sectional retrospective study included 607 premenopausal women who had undergone coronary angiography [25] and also in hospital-based case-control study conducted in patients attending the affiliated hospital of Qingdao university, China. [26] Hyperuricaemia predisposes to the progress of hypertension and oxidative stress may increase and generates free radicals, which eventually acts as source of future cardiovascular disease risk.…”
Section: Discussionsupporting
confidence: 87%
“…[23] The increased serum uric acid level was also found to be associated with the severity of CAD in both men and women. In the present study significant relationship was observed between uric acid and CAD similar results were reported from a study with 1012 patients who underwent coronary angiography in Turkish population, [24] cross-sectional retrospective study included 607 premenopausal women who had undergone coronary angiography [25] and also in hospital-based case-control study conducted in patients attending the affiliated hospital of Qingdao university, China. [26] Hyperuricaemia predisposes to the progress of hypertension and oxidative stress may increase and generates free radicals, which eventually acts as source of future cardiovascular disease risk.…”
Section: Discussionsupporting
confidence: 87%
“…Uric acid and prognosis in angiography-proven coronary artery disease [15] (Gjin Ndrepepa) In our study that included 13 273 patients with angiographic confirmation of coronary artery disease (CAD) treated with percutaneous coronary intervention, we concluded that uric acid (UA) predicted an increased risk of cardiac and all-cause mortality across all subsets of the patients and that the association between UA and cardiac or all-cause mortality had a 'J-shaped' pattern with lowest risk of death in patients with UA levels between 5Á17 and < 6Á76 mg/dL. Since its publication, evidence has gathered that elevated UA level is associated CAD and/or increased incidence of cardiovascular adverse events [16][17][18][19][20]. One recent study in which UA was measured in 3315 patients showed that UA was associated with CAD and it was causally related to adverse cardiovascular events, especially sudden cardiac death [16].…”
Section: Al-daghri)mentioning
confidence: 99%
“…59 In a cross-sectional retrospective study of 607 premenopausal women who had undergone coronary angiography, serum uric acid levels were associated with the presence of CAD. 60 This finding was confirmed in patients with transient ischemic attacks or stroke; an elevated uric acid level independently predicted long-term CAD in women but not men. 61 It is as yet unclear whether lowering uric acid levels reduces CVD risk.…”
Section: Uric Acid Levelmentioning
confidence: 75%